Analysis of the Application of Environmental Accounting as One of Social Accountability at the One Legian Hotel - N P Paramitha Ardy Rahayu; I M Sudana; N N Yintayani (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
In the field of accounting, there is Green Accounting or environmental accounting where there are five stages of environmental cost allocation process, namely identification, recognition, measurement, presentation, and disclosure. This research is descriptive qualitative research located at The ONE Legian Hotel. Where the primary data used are inter- views while the secondary data used are archives and written documents. This study uses a constant comparative analysis that aims to compare the stages of environmental cost allocation at The ONE Legian Hotel with the 2019 Financial Reporting Conceptual Framework. The result of this research is that The ONE Legian Hotel has implemented an environmental cost allocation which consists of identification by dividing into two, environmental/natural costs and social environmental costs, then the recognition using the accrual basis method, measurement using rupiah with realization the budget that has been determined by the company, in the presentation where these environmental costs have been presented in the income statement, in the other expenses section or in the POMEC subsection for environmental/natural costs and the human resource subsection for social environmental costs. However, the disclosure has not been carried out, where detailed environmental costs are not included in the financial statements, so users of financial statements don’t know the details of the environmental costs.